Transboundary animal diseases: Research and development priorities for resilient agrifood systems - Hung Nguyen-Viet (International Livestock Research Institute, 2023)
The Food and Agriculture Organization of the United Nations defines transboundary animal diseases (TADs) as animal diseases that are of significant economic, trade and/or food security importance for a considerable number of countries; which can easily spread to other countries and reach epidemic proportions; and where control/management, including exclusion, requires cooperation between several countries.